2011
DOI: 10.1007/s11095-011-0404-y
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion Microstructure Influences the Skin Delivery of an Hydrophilic Drug

Abstract: The structure of microemulsions is of relevance for skin absorption. The water-continuous structures allow faster transport of hydrophilic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 41 publications
2
33
0
1
Order By: Relevance
“…It was seen (Table 4.4) that the highest permeability of naproxen was obtained from OA and EU nanoemulsion formulations, which may be due to high solubility of naproxen in the stratum corneum from these formulations compared with controls. Naoui et al found significant differences in the amount of caffeine stored in the stratum corneum (202). It was previously claimed that diffusional resistance in the dermal matrix could significantly decrease the permeability of lipophilic solutes (203).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was seen (Table 4.4) that the highest permeability of naproxen was obtained from OA and EU nanoemulsion formulations, which may be due to high solubility of naproxen in the stratum corneum from these formulations compared with controls. Naoui et al found significant differences in the amount of caffeine stored in the stratum corneum (202). It was previously claimed that diffusional resistance in the dermal matrix could significantly decrease the permeability of lipophilic solutes (203).…”
Section: Discussionmentioning
confidence: 99%
“…The O/W nanoemulsion is conductive, however, W/O emulsions show much greater resistance. Therefore, the conductivity switched between two plateaus corresponding to water-continuous and oil-continuous structure (202).…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 99%
See 3 more Smart Citations